Quantitative Proteomic Analysis for High- and Low-Aflatoxin-Yield Aspergillus flavus Strains Isolated From Natural Environments - Li, Tao; Zhang, Zhaowei; Wang, Yu; Li, Ying; Zhu, Jiang; Hu, Rui; Yang, Yunhuang; Liu, Maili (Frontiers in Microbiology, 2021)
The molecular mechanisms underlying aflatoxin production have been well-studied in strains of the fungus Aspergillus flavus (A. flavus) under artificial conditions. However, aflatoxin biosynthesis has rarely been studied in A. flavus strains isolated from field conditions with different aflatoxin-producing ability. In the present study, tandem mass tag (TMT) labeling and high-performance liquid chromatography (HPLC) coupled with tandem-mass spectrometry analysis were used for proteomic quantification in natural isolates of high- and low-aflatoxin-yield A. flavus strains. Additionally, findings obtained using the TMT-labeling method were validated using the high-resolution multiple reaction monitoring (MRM-HR) method. In total, 4,363 proteins were quantified, among which 1,045 proteins were differentially expressed between the high- and low-aflatoxin-yield A. flavus strains. Bioinformatics analysis showed that the up-regulated proteins were significantly enriched in carbon-related metabolism and the biosynthesis of secondary metabolites, whereas the down-regulated proteins were enriched in oxidative phosphorylation. Moreover, GST proteins were found to be significantly down-regulated in high-yield A. flavus strains; this result contradicted previous findings obtained from A. flavus strains grown under artificial conditions. In summary, our study provides novel insights into aflatoxin regulation in A. flavus under field conditions and could facilitate the development of various strategies for the effective control of aflatoxin contamination in food crops.